2013
DOI: 10.4103/0301-4738.124737
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of amblyopia in children undergoing nasolacrimal duct irrigation and probing

Abstract: Purpose:To investigate ambylopia and amblyopia risk factors of children who underwent nasolacrimal duct (NLD) irrigation and probing for congenital nasolacrimal duct obstruction (CNLDO).Materials and Methods:The medical records of patients who had undergone NLD irrigation and probing for CNLDO at an age of 3 years or younger were reviewed, and 51 of the patients were recalled between October 1 and December 31, 2011 for a detailed ophthalmic examination to determinate amblyopia or amblyopia risk factors. Amblyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Ramkumar et al 8 studied 142 children with CNLDO and reported the prevalence of amblyopia risk factors in 20% (n=28). Similarly, Ozgur et al 9 reported amblyopia risk factors in 27.5% (n=14) among their cohort of 51 patients, and Kim et al 10 reported the risk factors in 35% (n=9) among their cohort of 26 patients. Siddiqui et al 11 studied 161 patients of CNLDO and reported a statistically significant higher incidence of refractive errors in patients with unilateral CNLDO as compared to bilateral cases.…”
Section: Discussionmentioning
confidence: 86%
“…Ramkumar et al 8 studied 142 children with CNLDO and reported the prevalence of amblyopia risk factors in 20% (n=28). Similarly, Ozgur et al 9 reported amblyopia risk factors in 27.5% (n=14) among their cohort of 51 patients, and Kim et al 10 reported the risk factors in 35% (n=9) among their cohort of 26 patients. Siddiqui et al 11 studied 161 patients of CNLDO and reported a statistically significant higher incidence of refractive errors in patients with unilateral CNLDO as compared to bilateral cases.…”
Section: Discussionmentioning
confidence: 86%
“…Bilateral obstruction, occurring in 9–47.5% [ 3 , 4 , 9 , 11 , 18 – 20 , 23 , 26 29 , 31 , 33 , 34 , 36 , 38 – 40 ] may indicate a more complicated cause of the condition, create greater technical difficulties during procedures performed under local anesthesia, and thus affect the obtainment of less-satisfactory results, which is also confirmed by our study and reports by other researchers [ 20 , 36 ]. Dietze et al [ 43 ] suggest that patients with trisomy 21, allergic rhinitis/seasonal allergies, history of an upper respiratory tract infection within 1 month and obstructive sleep apnea may be correlated with a higher risk of failure with a probing.…”
Section: Discussionmentioning
confidence: 99%
“…Abundant lacrimal meniscus and mucopurulent discharge which persists on the surface of the cornea may lead to blurring of vision and interferes with the clear focusing of images on the retina, which is critical for emmetropization [22]. Several authors have confirmed an increased risk for anisometropia and amblyopia in patients with CNLDO (especially long-term untreated obstructions) [22][23][24][25]. However, the effect of long-term epiphora on visual development in children is debatable and some studies reported no significant differences between children with CNLDO and general population [17,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…It is also proposed that this anisometropia is refractory. However, recent studies reveal that this is not necessarily true [51], which will be discussed in a while.…”
Section: Cnldo and Its Effect On The Visual Systemmentioning
confidence: 93%
“…The prevalence of anisometropia in the general pediatric population ranges from 2.3 to 3.4%, based on literature review [58]. Amblyopia has been reported to occur in approximately 1.6-3.6% of the normal population [51,58]. The prevalence is even higher in medically underserved populations with reported rate as high as 22.7% [59].…”
Section: Visual System Anisometropia and Amblyopiamentioning
confidence: 99%